Klotho’s impact on diabetic nephropathy and its emerging connection to diabetic retinopathy - Tang, Anqi; Zhang, Yu; Wu, Ling; Lin, Yong; Lv, Lizeyu; Zhao, Liangbin; Xu, Bojun; Huang, Youqun; Li, Mingquan (Frontiers in Endocrinology, 2023)
Diabetic nephropathy (DN) is the leading cause of end-stage renal disease worldwide and is a significant burden on healthcare systems. α-Klotho (Klotho) is a protein known for its anti-aging properties and has been shown to delay the onset of age-related diseases. Soluble Klotho is produced by cleavage of the full-length transmembrane protein by a disintegrin and metalloproteases, and it exerts various physiological effects by circulating throughout the body. In type 2 diabetes and its complications DN, a significant decrease in Klotho expression has been observed. This reduction in Klotho levels may indicate the progression of DN and suggest that Klotho may be involved in multiple pathological mechanisms that contribute to the onset and development of DN. This article examines the potential of soluble klotho as a therapeutic agent for DN, with a focus on its ability to impact multiple pathways. These pathways include anti-inflammatory and oxidative stress, anti-fibrotic, endothelial protection, prevention of vascular calcification, regulation of metabolism, maintenance of calcium and phosphate homeostasis, and regulation of cell fate through modulation of autophagy, apoptosis, and pyroptosis pathways. Diabetic retinopathy shares similar pathological mechanisms with DN, and targeting klotho may offer new insights into the prevention and treatment of both conditions. Finally, this review assesses the potential of various drugs used in clinical practice to modulate klotho levels through different mechanisms and their potential to improve DN by impacting klotho levels.